Avaliação de impactos ambientais na instalação de um parque eólico em Pereiro-CE - Firmino, Cristiano Benevides (Universidade Federal Rural do Semi-Árido, 2017)
The need to verify possible environmental impacts, is present in any undertaking of energy generation character, mostly those that will be implanted in places of great environmental preservation. The County of Pereiro/CE currently coexist with a scenario of degradation of the environment, this being the result of the neglect of the population and undertaking projects. The present research has by objective promote a discussion about the possible environmental impacts coming from the implantation of an wind farm in the County of Pereiro/CE, looking for analyze the viability of the installation of an wind farm in a mountain range at Pereiro/CE, by identification, measurement an devaluation of the environmental impacts coming from the installation phase. The method of analysis of environmental impacts was the interaction matrix, considering the existing data and the possibility of obtaining information when possible. Applying the methodology was possible identify 274 impacts (positives and negatives) in the installation phase, and of these, 119 were evaluated as significant, where 49 are related to the activities that can alter the physical and chemical characteristics of the location, these being the ones that must be sued greater attention to mitigation, due to the large number of significant impacts on this aspect. The results were satisfactory and can serve as a basis to future studies, even for the companies that are searching the implantation from this undertaking in the locality, in view of the presentation of the mitigating measures for the impacts generated during the installation phase presented to the local community for greater acceptance of the project, as well as exposing the growth that the commercial and energy sectors can provide after this installation.
Keywords: Energia limpa; Setor energético; Matriz de interação; Preservação ambiental; clean energy; growth in the energy sector; interaction matrix; environment preservation; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA